Financial stability analysis: insights gained from consolidated banking data for the EU - Stefano Borgioli; Ana Cláudia Gouveia; Claudio Labanca (European Central Bank (ECB), 2013)
This occasional paper explores the Consolidated Banking Data (CBD), a key component of the ECB statistical toolbox for financial stability analysis. We show that non-consolidated, host-country Monetary Financial Institutions (MFI) balance sheet data, which constitutes a key source of input into monetary analysis, are a rather weak proxy for consolidated, home-country data and therefore cannot easily substitute CBD for the purposes of macro-prudential assessment. In addition, it is argued that, notwithstanding the relevance of large banks, medium-sized and small banks must also be taken into account in financial stability analysis, given their relevance in several EU countries and their different business models. A discussion follows on how aggregate data, broken down by bank size, can be used to complement micro data, in particular by signalling where and what to look for, again highlighting the differences between large banks on the one hand and small and mediumsized banks on the other.
Keywords: E13; E31; E50; 330; banking indicators; consolidated banking data; macro-prudential analysis; Finanzsystem; Wirtschaftsindikator; Bankrechnungslegung; EU-Staaten